Erratum to: Genetic Counselling for maternally inherited mitochondrial disorders. - Poulton, J; Finsterer, J; Yu-Wai-Man, P (Springer, 2017)
There is information omitted from the “Result” section of the Abstract. The corrected part of the Abstract should read: Results: Fetal dry weight and placental efficiency (embryo/placental fresh weight) were positively correlated (r = 0.53, P = 0.0001). Individual placental dry weight was reduced by LPD (P = 0.003), as was the expression of amino acid transporter Slc38a2 and of growth factor Igf2. Placental water content, which is regulated by active transport of solutes, was increased by LPD (P = 0.0001). However, placental ATP content was also increased (P = 0.03).